2021
DOI: 10.1002/app.50590
|View full text |Cite
|
Sign up to set email alerts
|

Rheological behavior and morphology of poly(lactic acid)/low‐density polyethylene blends based on virgin and recycled polymers: Compatibilization with natural surfactants

Abstract: Blends based on poly(lactic acid) and low-density polyethylene were compatibilized exploiting an innovative strategy involving the introduction of different mixtures of two sustainable liquid surfactants characterized by dissimilar hydrophilic-lipophilic ratios. The compatibilization method was first applied on blends made of virgin polymers, aiming at assessing the surfactant mixture inducing a more significant morphology refinement. Besides, to verify the effectiveness of the selected compatibilizers on recy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Casamento et al 158 observed the compatibilization effect of PLA/LDPE blends by using two natural surfactants. The ratio of surfactants Tween 80/Span 80 (72:28 wt %) was characterized by hydrophilic−lipophilic ratios.…”
Section: Pla-based Blends and Compositesmentioning
confidence: 99%
“…Casamento et al 158 observed the compatibilization effect of PLA/LDPE blends by using two natural surfactants. The ratio of surfactants Tween 80/Span 80 (72:28 wt %) was characterized by hydrophilic−lipophilic ratios.…”
Section: Pla-based Blends and Compositesmentioning
confidence: 99%
“…In addition, there has been a rise in the usage of plastics for personal protective equipment (PPE) and single-use plastic (SUP) in packaging due to the Coronavirus pandemic [2][3][4][5][6][7][8][9]. Besides end-of-life products, production scraps also produce a large quantity of plastic waste [10].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical recycling (the process of grounding down and reprocessing waste plastics), feedstock recycling (converting long polymer chains into shorter components used as feedstock), and energy recovery (the incineration of waste plastics) are the main recycling routes. Mechanical recycling is the most widely used because of its relative ease and economy [6,7,10]. However, mechanical stress, heat, oxidation, and ultraviolet radiation affect the properties of recycled polymers during reprocessing and lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, significant differences in the slopes of the curves appear at low frequencies, i.e., with the appearance of a shoulder in the PLA_PBAT_15 blend. This behavior is very likely to be due to a droplet/matrix morphology [ 50 , 51 , 52 , 53 ] and it substantially disappears at higher compositions. This could be attributed to the formation of more complex morphologies showing slow relaxation dynamics [ 51 , 52 , 53 ] and will be further investigated and discussed in the following morphological characterization section.…”
Section: Resultsmentioning
confidence: 99%